Brokers of modernity : East Central Europe and the rise of modernist architects, 1910-1950 (2019)
In 1925 a rare type of building made its appearance in the literary world: a house entirely constructed of glass, prefabricated yet individualized, light but stable, flat- roofed but with walls which changed colour according to the surrounding land- scape. The cavity walls allowed for the movement of water – warm in winter-time and cold in summer-time – which generated a comfortable indoor temperature while the presence of vents ensured the movement of fresh air. The circulating water also guaranteed continuous cleansing of walls and floors. Even the furniture, also made out of glass, underwent this continuous cleansing ritual: These houses of glass “spread like the plague once people found out about it. Who would want to live in a decaying, mouldy wooden sty eaten away by dry rot, or in a hovel that’s a breeding ground for rheumatism, tuberculosis and scarlet fever